Analisis Manajemen Sarana dan Prasarana dalam Mendukung Lingkungan Belajar yang Kondusif - Endang Mbatu; Ineke Ully; Agnes Lede; Kristo Tanhi; Margarita Punuf; Yanti Y E Solle (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2026)
Facilities and infrastructure are essential components that determine the success of the teaching and learning process in schools, including the creation of a conducive learning environment. This study aims to analyze how the management of educational facilities and infrastructure—covering planning, procurement, distribution, inventory, utilization, maintenance, and disposal—contributes to supporting a conducive learning environment. The method used is a library research approach, in which data were collected by reviewing relevant journals, books, and other scholarly sources. The results show that effective management of facilities and infrastructure, implemented through careful planning, transparent procurement, scheduled utilization, and regular maintenance, plays a significant role in creating a safe, comfortable, and supportive learning atmosphere. Moreover, professional administrative management and adequate human resources are equally important in sustaining a conducive school environment. The study concludes that optimal management of facilities and infrastructure, supported by competent human resources, is a key factor in improving student motivation, learning achievement, and the overall quality of education.